2018
DOI: 10.1186/s13104-018-3239-3
|View full text |Cite
|
Sign up to set email alerts
|

A case series on common cold to severe bronchiolitis and pneumonia in children following human metapneumovirus infection in Sri Lanka

Abstract: ObjectivesThe prevalence of hMPV infections in Sri Lanka has not been reported and here we report a case series of hMPV infection in children less than 5 years. Patients with ARTI were included from Teaching Hospital, Anuradhapura from March 2013 to August 2014. Indirect fluorescence assay was performed on nasopharyngeal aspirates for the identification of respiratory viruses [respiratory syncytial virus (RSV), parainfluenza virus 1, 2 and 3, influenza A and B and hMPV]. Moreover, reverse transcriptase-polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…[9] Co-infection with both viruses can also occur, resulting in a more complicated and serious clinical disease. [318] In addition to the pediatric population, studies have also found hMPV to infect adults[19] and elderly people. [20] In terms of transmission, hMPV spreads through contact with contaminated secretions, i.e., droplet, aerosol or fomites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9] Co-infection with both viruses can also occur, resulting in a more complicated and serious clinical disease. [318] In addition to the pediatric population, studies have also found hMPV to infect adults[19] and elderly people. [20] In terms of transmission, hMPV spreads through contact with contaminated secretions, i.e., droplet, aerosol or fomites.…”
Section: Introductionmentioning
confidence: 99%
“…In young children, infections are usually not asymptomatic, and bronchiolitis, with or without pneumonia, is the most common associated presentation. [182021] Other reported conditions include bronchial asthma exacerbation, otitis media, pneumonitis, flu-like illness and community-acquired pneumonia. [9] In adults, hMPV has been associated with bronchitis, pneumonia and exacerbations of both bronchial asthma and chronic obstructive pulmonary disease.…”
Section: Introductionmentioning
confidence: 99%
“…Data obtained were double entered into a spreadsheet database prepared with Microsoft ® Excel and compared and cleaned for wrong entries. Statistical analysis was done using SAS version 9.1 (SAS, 2005, New Jersey) 34 . Association of each of the categorical variable with response variable was assessed by Chi-square test.…”
Section: Methodsmentioning
confidence: 99%
“…Human Metapneumovirus (HMPV) remains one of the most common viral causes of acute respiratory tract infections, especially in children, elderly, and immunocompromised populations. Clinical symptoms can range from mild respiratory disease to severe bronchiolitis and pneumonia, some of which require hospitalization [ 15 , 16 ]. Because the lungs are one of the largest mucosal surfaces in the human body and contain mucus with a vast variety of mucin proteins, further studies are necessary to define the role of these various mucins, both in normal functioning lungs, as well as injured and infected lungs.…”
Section: Discussionmentioning
confidence: 99%